Teknik Konservasi Energi Pada Pompa Submersible Dengan Menggunakan Variable Frequency Drive - M.Eng, haji sofyar (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2017)
Energy conservation is beneficial not only to reduce consumption and the cost of energy consumption, but also to give a better impact on the environment. In this study a simulation model is created which is a reflection of the relationship con-dition between variable frequency drive (VFD), induction motor and centrifugal pump. By creating a simulation model will be able to know the potential savings that will be provided if the variable frequency drive is used.